Investigation on the performance of tetraglyme based solid copolymer electrolytes for solid state electrical double layer capacitors (EDLCs) / Sharmilah Sinasamy - Sharmilah , Sinasamy (2021)
Solid polymer electrolytes (SPEs) have been the focus of intensive research due to their large demand in applications such as electrochemical capacitors, fuel cells, solar cells and batteries. They have shown many advantages such as wider electrochemical potential window, good thermal stability, low volatility and easy handling. Due to these advantages, SPEs have great potential in energy storage applications. Usually, SPEs suffer from poor conductivity, which hinders its performance for energy storage applications. In order to enhance the conductivity of the SPEs, the host polymer incorporated with salt to provide ions for conductivity, ionic liquid to enhance the conductivity and fillers to increase the thermal and electrical stability. Herein, Poly (vinylidene fluoride-hexafluropropene) PVDF-HFP used as a host polymer with LiCIO4 salt to provide ions and tetraglyme as an additive. SPEs prepared by facile solution casting technique and its performances were evaluated for electric double layer supercapacitor (EDLC). The effects of tetraglyme (Diethylene glycol dimethyl ether) on the enhancement of ionic conductivity and on the performance of EDLC was investigated. Conductivity studies revealed that, tetraglyme significantly improvised the ionic conductivity of the SPEs by assisting ion mobility in the host polymer and has shown high ionic conductivity at room temperature. The highest ionic conductivity value of 1.34 x 10-3 Scm-1 is achieved upon addition of 20 wt. % tetraglyme (STG20). Temperature-dependant ionic conductivity studies confirmed that SPE system follows Arrhenius thermal activation model. The crystallinity and complexation of the SPEs were characterized using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy, respectively. XRD results confirmed the complexation of LiCIO4 salts with the host polymer. FTIR spectra presented that tetraglyme and LiCIO4 salt successfully incorporated with the host polymer. The electrochemical performance of prepared SPEs evaluated by cyclic voltammetry, galvanostatic charge discharge and electrochemical impedance spectroscopy. It was found that SPE incorporated with tetraglyme displayed excellent performance for EDLC compared to the SPE without tetraglyme. From the electrochemical studies, STG 20 achieved the maximum specific capacitance of 14.06 F/g, which is larger than STG 30 (sample with 30 wt. % tetraglyme) (4.87 F/g) and ST30 (0.11 F/g) at 100 mA/g.